2013
DOI: 10.1097/pec.0b013e3182999bcd
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of New Interventions for Peripheral Intravenous Cannulation of Children

Abstract: Near-infrared light devices might be efficacious in selected subpopulations, but the available evidence does not support an overall benefit in the pediatric population. Transilluminators modestly improve pediatric PIVC, but the clinical significance of this benefit is questionable. Nitroglycerin ointments may increase the risk of PIVC failure and are associated with adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 31 publications
1
25
1
Order By: Relevance
“…71 However, recommendations for other visualization techniques in pediatric populations, including NIR light (vessel visualization) and ECG (catheter-tip confirmation) device use, were scant. Use of NIR light devices may be efficacious in selected high-risk subpopulations 102 and may modestly improve first-attempt success rates 77,104,110 ; however, the current evidence does not support an overall benefit 74 or a benefit that is better than non-image-guided methods. 104 Similarly, low levels of evidence prevent the recommendation of ECG assistance for PICC placement 105 ; however, one study also found higher first-attempt success and correct tip position success by using intracavitary ECG PICC insertion compared to landmark techniques.…”
Section: Vessel Visualizationmentioning
confidence: 67%
“…71 However, recommendations for other visualization techniques in pediatric populations, including NIR light (vessel visualization) and ECG (catheter-tip confirmation) device use, were scant. Use of NIR light devices may be efficacious in selected high-risk subpopulations 102 and may modestly improve first-attempt success rates 77,104,110 ; however, the current evidence does not support an overall benefit 74 or a benefit that is better than non-image-guided methods. 104 Similarly, low levels of evidence prevent the recommendation of ECG assistance for PICC placement 105 ; however, one study also found higher first-attempt success and correct tip position success by using intracavitary ECG PICC insertion compared to landmark techniques.…”
Section: Vessel Visualizationmentioning
confidence: 67%
“…Peripheral venous cannulation is the commonest, and probably the most important invasive procedure practised in hospitals. Principles are summarised in Table .…”
Section: Peripheral Venous Cannulationmentioning
confidence: 99%
“…In our study, nearly all patients with initial insertion failure experienced successful PIV insertion by the VAT, who used POCUS for 50% of patients to evaluate peripheral veins before attempts, and for 40% during active PIV insertion. POCUS‐enhanced PIV insertion has been supported in recent studies regarding DIVA in both adult and pediatric patients . We intend to use these results to inform an interventional study involving the use of POCUS by PED providers in patients at risk of prolonged PIV insertion or failure who require vascular access in the resuscitation area of our PED.…”
Section: Discussionmentioning
confidence: 76%